Application of the generalizability theory in the services evaluation in sports management - Gálvez-Ruiz, P.; Grimaldi-Puyana, M.; Fernández-Gavira, J.; Sánchez-Oliver, A. Jesús (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
This paper addresses from the use of the Generalizability Theory (TG) the optimization of resources in sports management. We used a design structure composed of the facets users (U), activities (A), scales (E) and items (I), following not orthogonal design, partially nested and multifaceted, within the General Linear Model. 537 participants (32.11 ± 11.11 years) completed the Questionnaire of Evaluation of the Perceived Quality in Sports Services obtaining excellent results both indexes of reliability (ξρ²(δ) > 0.98) and generalizability (ξρ²(Δ) > 0.98). The optimization showed that half of participants and fewer activities, we obtain a high degree of generalization and at the same time, reduced the total number of observations, being important for future studies which will facilitate the evaluation of sport service more efficiently.